The Human SLC1A5 Neutral Amino Acid Transporter Catalyzes a pH-Dependent Glutamate/Glutamine Antiport, as Well - Scalise, Mariafrancesca; Mazza, Tiziano; Pappacoda, Gilda; Pochini, Lorena; Cosco, Jessica; Rovella, Filomena; Indiveri, Cesare (Frontiers in Cell and Developmental Biology, 2020)
ASCT2 is a neutral amino acid transporter, which catalyzes a sodium-dependent obligatory antiport among glutamine and other neutral amino acids. The human ASCT2 over-expressed in P. pastoris and reconstituted in proteoliposomes has been employed for identifying alternative substrates of the transporter. The experimental data highlighted that hASCT2 also catalyzes a sodium-dependent antiport of glutamate with glutamine. This unconventional antiport shows a preferred sidedness: glutamate is inwardly transported in exchange for glutamine transported in the counter direction. The orientation of the transport protein in proteoliposomes is the same as in the cell membrane; then, the observed sidedness corresponds to the transport of glutamate from the extracellular to the intracellular compartment. The competitive inhibition exerted by glutamate on the glutamine transport together with the docking analysis indicates that the glutamate binding site is the same as that of glutamine. The affinity for glutamate is lower than that for neutral amino acids, while the transport rate is comparable to that measured for the asparagine/glutamine antiport. Differently from the neutral amino acid antiport that is insensitive to pH, the glutamate/glutamine antiport is pH-dependent with optimal activity at acidic pH on the external (extracellular) side. The stimulation of glutamate transport by a pH gradient suggests the occurrence of a proton flux coupled to the glutamate transport. The proton transport has been detected by a spectrofluorometric method. The rate of proton transport correlates well with the rate of glutamate transport indicating a 1:1 stoichiometry H+: glutamate. The glutamate/glutamine antiport is also active in intact HeLa cells. On a physiological point of view, the described antiport could have relevance in some districts in which a glutamate/glutamine cycling is necessary, such as in placenta.